Removal performance and mechanism of typical amino acids in water by the peroxymonosulfate/Fe3O4 nanoparticles. Issue 2 (27th October 2021) - Luo, Yuye; Liu, Cheng; Zhao, Meiqi; Mehmood, Tariq
Abstract: Dissolved organic nitrogen (DON) as precursors of nitrogenous disinfection byproducts (N-DBPs) has become a serious issue for drinking water treatment. Here, Fe3 O4 /peroxymonosulfate (PMS) system was used to examine the amino acid removal and formation of N-DBPs in the system and the corresponding mechanisms. Results showed a remarked variation in removal efficiency of three typical amino acids, i.e., glutamate (78%), histidine (53%) and phenylalanine (27%) in Fe3 O4 /PMS system at optimum conditions (0.1 g/L Fe3 O4, 1.5 mM PMS, 1 h). Notably, Fe3 O4 /PMS treatment led to dichloroacetonitrile (DCAN) formation caused by the chlorination of glutamate, phenylalanine and histidine being reduced by 53.3%, 9.7% and 41.9%, respectively. The degradation and subsequent N-DBPs formation in the Fe3 O4 /PMS system mainly depended on the types and properties of the amino acids. The formation of dichloroacetamide (DCAcAm) exhibited different trends, which may be due to the different R group structure of the three amino acids and the special aromaticity of the imidazole ring in the histidine side chain that facilitates its quick electrophilic substitution and ring-opening reaction. This study highlights that the Fe3 O4 /PMS system is a promising strategy to remove DON and efficiently eliminate N-DBPs formation in the drinking water treatment process depending on the amino acid type. HIGHLIGHTS: Fe3 O4 could effectively catalyze PMS for the degradation of three typical amino acids. The formation potential of DCAN and DCAcAm by amino acids in the Fe3 O4 /PMS system was clarified. Degradation pathways and intermediates of amino acids were also analyzed.